Enriching the lives of children with acquired brain injury and their caregivers: experiences from peer mentorship sports camps - Wedege, Pia; Mæland, Silje; Divanoglou, Anestis; Abrahamsen, Frank Eirik (Frontiers in Rehabilitation Sciences, 2024)
Peer-based community interventions have shown promise in improving health management and fostering coping skills and psychosocial functioning among individuals with a disability. Active Rehabilitation camps are examples of peer-based community interventions that provide structured, time-limited peer mentorship in conjunction with sports and leisure activities. These camps hold potential benefits for individuals with acquired neurological injury. However, the specific impact of Active Rehabilitation camps on children or individuals with acquired brain injury remains unexplored. In this longitudinal, qualitative study, we explored children with an acquired brain injury and their caregivers' experiences with an Active Rehabilitation camp in Norway through observations and interviews with nine children and ten caregivers. Using an abductive thematic analysis, we identified an overarching theme: Active Rehabilitation peer mentorship camps enrich the lives of children with acquired brain injury and their caregivers. The theme contains three sub-themes: (1) Interacting with peers made me wiser, (2) Nudging from peer mentors made me feel better, and (3) A sense of companionship through meeting peers. Peer mentorship, sports and leisure activities, and the safe camp atmosphere benefitted children with acquired brain injury and their caregivers. The children gained knowledge, motivation, and self-worth, and their caregivers had greater impetus to prioritize their children's independence. Meeting peers and peer mentors led to friendships and sustained social connections. The Self-Determination Theory was of assistance in explaining the informants' experiences. Active Rehabilitation camps provide children with acquired brain injury and their caregivers with an opportunity to develop better coping skills, improve psychological functioning, and build more robust social networks.